Pengaruh Produk dan Promosi Terhadap Keputusan Menabung Tabungan Simpedes di PT. Bank Rakyat Indonesia (PERSERO) Tbk. Cabang Semarang Pattimura - Robertus Andy Nugroho; Nawazirul Lubis; Apriatni Endang Prihartini (Universitas Diponegoro, 2014)
Saving decisions are actions that are directly involved in acquiring businesses, products and services,including determining the decision-making process of saving and to follow the action. This study was conducted todetermine the effect of product and promotion to save Savings Simpedes decision in PT. People's Bank Indonesua(Persero) Tbk. Semarang Pattimura branch. In this study using a non-probability sampling technique sampling withaccidental sampling so that the user can take the 100 respondents Simpedes savings services. Analysis of the dataused is regression. The results showed that there is a positive and significant effect between the product and thepartial and promotion together towards saving decision